Savvy silvers : a campaign to teach senior citizens aged 50 and above learn how to use their smartphones efficiently and subsequently, independently - Teo, Elissa Shiting (2016)
Savvy Silvers is a campaign to help senior citizens aged 50 and above learn how to use their smartphones efficiently, and subsequently, independently. It also aimed to dispel fear and increase confidence for senior citizens who are still hesitant about embracing smartphone technology. Savvy Silvers stemmed not only from personal experiences with senior citizens, but is also in accordance with Singapore’s digital inclusion efforts and a national move towards being a Smart Nation. To find out what senior citizens wanted to learn, we conducted a survey and hence designed a comprehensive smartphone curriculum. This culminated into a series of lessons where senior citizens learnt how to use their smartphones in a conducive and interactive environment in the heartlands. Intergenerational learning between senior participants and youth volunteers was also one of the key features of these smartphone lessons. This report examines the rationale for this campaign, discusses the executional tactics implemented in rolling out the campaign and the impacts of these strategies used. Significant achievements and recommendations to widen the scope of the project are also discussed. The lifespan of Savvy Silvers will be extended beyond its intended duration as partners including the People’s Association and the Infocomm Development of Authority have expressed interest in rolling out the Savvy Silvers smartphone lessons to other parts of Singapore, developing it into a nation-wide movement.